Komposisi By-catch Perikanan Lele Laut (Famili Plotosidae) di Perairan Teluk Kolono, Sulawesi Tenggara - Asriyana, Asriyana; Halili, Halili; Irawati, Nur (JSIPi (Jurnal Sains dan Inovasi Perikanan) (Journal of Fishery Science and Innovation), 2020)
The by-catch on the gill net fisheries is the current global fisheries problems and issues. This study aimed to analyze by-catch composition of fishery eel catfish (Plotosidae) in Kolono Bay, Southeast Sulawesi. Sampling was done monthly from April to July 2019, with bottom experimental gillnets of ¾, 1¼, 1½, 1 ¾, and 2 inches mesh sizes. The highest proportion of catches was found in by-catch (62.72%) than the main target, the family Plotosidae (37.28%). The by-catch includes 23 families consisting of two groups namely the useable by-catch 55.57% (19 families) and discarded by-catch 7.15% (4 families). Out of these 23 families, 44 species belong to the Least Concern (LC) and 24 species Not Evaluated (NE) categories on the IUCN red list 2019. The results showed that the use of bottom gillnets in eel catfish fisheries has a low selectivity which is characterized by high diversity and low dominance of by-catch.